Opportunities and challenges related to ferroptosis in glioma and neuroblastoma - Chi, Huizhong; Li, Boyan; Wang, Qingtong; Gao, Zijie; Feng, Bowen; Xue, Hao; Li, Gang (Frontiers in Oncology, 2023)
A new form of cell death known as ferroptosis is characterized by the peroxidation of lipids in response to iron. Rapid progress in the research of ferroptosis in malignant CNS tumors has promoted the use of ferroptosis in related therapy. The study gives a review on the findings on ferroptosis therapy in glioblastoma and neuroblastoma and outlines the mechanisms involved in ferroptosis in malignant CNS tumors. We summarize some recent data on traditional drugs, natural compounds and nanomedicines as ferroptosis inducers in malignant CNS tumors and summarize some bioinformatics analyses of genes involved in ferroptosis. Moreover, we summarize some data concerning the association involving the micro-environment of the tumor immune system as well as TMZ drug resistance to ferroptosis. Finally, we discuss the future directions of ferroptosis research in malignant CNS tumors and the currently unresolved issues.